Improving Iturin A Production of Bacillus amyloliquefaciens by Genome Shuffling and Its Inhibition Against Saccharomyces cerevisiae in Orange Juice - Shi, Juran; Zhu, Xiaoyu; Lu, Yingjian; Zhao, Haizhen; Lu, Fengxia; Lu, Zhaoxin (Frontiers in Microbiology, 2018)
Genome shuffling is an effective method for the rapid improvement of the production of secondary metabolites. This study used the principle of gene shuffling to enhance the yield of iturin A produced by Bacillus amyloliquefaciens LZ-5. Improvements in lipopeptide yield were evident among four strains subjected to recursive protoplast fusion. The four strains were obtained through mutagenesis processes: nitrosoguanidine, ultraviolet irradiation, and atmospheric and room temperature plasma. A high yield strain with 179.22 mg/l of iturin A was obtained after two rounds of genome shuffling, which was a 2.03-fold increase compared with the wild strain. To evaluate the efficacy of iturin A for control of spoilage yeast in food, the anti-yeast efficacy of iturin A was evaluated in orange juice incubated with Saccharomyces cerevisiae. The juice treated with 0.76 mg/ml iturin A showed a significant (p<0.05) control on yeast population during the storage, similar to that of the 0.30 mg/ml natamycin. In addition, iturin A showed a tiny effect on chemical-physical characteristics of orange juice. Our results provide a basis for the application of antimicrobial lipopeptide in juice products.